SYSTEMATIC REVIEWS OF ECONOMIC EVALUATIONS IN HEALTH TECHNOLOGY ASSESSMENT: A REVIEW OF CHARACTERISTICS AND APPLIED METHODS. (22nd October 2018) - Luhnen, Miriam; Prediger, Barbara; Neugebauer, Edmund A.M.; Mathes, Tim
Abstract : Objectives: When making decisions in health care, it is essential to consider economic evidence about an intervention. The objective of this study was to analyze the methods applied for systematic reviews of health economic evaluations (SR-HEs) in HTA and to identify common challenges. Methods: We manually searched the Web pages of HTA organizations and included HTA-reports published since 2015. Prerequisites for inclusion were the conduct of an SR-HE in at least one electronic database and the use of the English, German, French, or Spanish language. Methodological features were extracted in standardized tables. We prepared descriptive statistical (e.g., median, range) measures to describe the applied methods. Data were synthesized in a structured narrative way. Results: Eighty-three reports were included in the analysis. We identified inexplicable heterogeneity, particularly concerning literature search strategy, data extraction, assessment of quality, and applicability. Furthermore, process steps were often missing or reported in a nontransparent way. The use of a standardized data extraction form was indicated in one-third of reports (32 percent). Fifty-four percent of authors systematically appraised included studies. In 10 percent of reports, the applicability of included studies was assessed. Involvement of two reviewers was rarely reported for the study selection (43 percent), data extraction (28 percent), and quality assessment (39 percent). Conclusions: The methods applied for SR-HEs in HTA and their reporting quality are very heterogeneous. Efforts toward a detailed, standardized guidance for the preparation of SR-HEs definitely seem necessary. A general harmonization and improvement of the applied methodology would increase the value of SR-HE for decision makers.